Correlation between grain boundaries, carbides and stress corrosion cracking of Alloy 690TT in a high temperature caustic solution with lead - Liu, Zhiyong; Hou, Qiang; Li, Chengtao; Li, Xiaogang; Shao, Jiamin (Corrosion science, 2018)
[Display omitted] •Cr-rich carbides are prone to oxidization in a lead contaminated aqueous solution.•Micro-cracks nucleate within oxides due to high strain concentration at RHGBs.•Σ3c boundary is less susceptible to SCC due to the combined effect of carbide and GB. The relationship between grain boundaries (GBs), carbides and stress corrosion cracking (SCC) of Alloy 690TT is investigated by immersion experiments using reverse U-bent specimens in a high temperature alkaline solution containing lead. The microstructures of blank samples and reverse U-bents are analyzed by scanning electron microscope with electron back scattering diffraction and transmission electron microscope. Detailed analyses indicate that Σ3 coherent twin boundaries are less susceptible to SCC than random high angle grain boundaries (RHGBs) due to the combined effect of carbides and GBs. A clear correlation and mechanism understanding relating GB character, carbide and susceptibility to SCC is established.